Advancing Pediatric Antibacterial Drug Development: A Critical Need to Reinvent our Approach. (8th February 2018) - Noel, Gary J; Nambiar, Sumathi; Bradley, John; ,
Abstract: The Clinical Trials Transformation Initiative convened with several groups in the pediatric antibacterial drug development community with the goal of identifying challenges and recommending ways to improve current practice. Attention to 5 major areas hold the promise of making new antibiotics available for use in children as soon as possible after they are approved for use in adults.